Evaluation of movement and brain activity. Issue 10 (October 2021) - Hallett, Mark; DelRosso, Lourdes M.; Elble, Rodger; Ferri, Raffaele; Horak, Fay B.; Lehericy, Stephan; Mancini, Martina; Matsuhashi, Masao; Matsumoto, Riki; Muthuraman, Muthuraman; Raethjen, Jan; Shibasaki, Hiroshi
Highlights: This review focuses on the most useful methods and techniques for the study of movement and movement disorders. Tools that can be used to study movement include kinematics, kinetics, and the underlying muscle activity with EMG. The brain activity driving movement can be studied with EEG, MEG, and functional MRI. Abstract: Clinical neurophysiology studies can contribute important information about the physiology of human movement and the pathophysiology and diagnosis of different movement disorders. Some techniques can be accomplished in a routine clinical neurophysiology laboratory and others require some special equipment. This review, initiating a series of articles on this topic, focuses on the methods and techniques. The methods reviewed include EMG, EEG, MEG, evoked potentials, coherence, accelerometry, posturography (balance), gait, and sleep studies. Functional MRI (fMRI) is also reviewed as a physiological method that can be used independently or together with other methods. A few applications to patients with movement disorders are discussed as examples, but the detailed applications will be the subject of other articles.